On-surface assembly of low-dimensional Pb-coordinated metal–organic structures1. Issue 14 (14th April 2015) - Lyu, Guoqing; Zhang, Ran; Zhang, Xin; Nian Liu, Pei; Lin, Nian
<x xml:space="preserve">Abstract</x> Porphyrin-based one-dimensional chains, ladders, and two-dimensional networks incorporating the p-block element Pb are assembled on a Au(111) surface.